How Regional Economic Growth, Population, and Manufacturing Value-Added Contribute to Regional Labor Force Participation - Alfarisy, Muhammad Farid (Universitas Muhammadiyah Yogyakarta, 2025)
This study investigates the relationship between manufacturing value-added, GRDP (Gross Regional Domestic Product), and population growth on the labor participation rate in the region. The sample comprises 16 provinces in total. It consists of 10 provinces that experienced economic growth rates lower than the national growth rate between 2017 and 2019. The remaining six provinces have economic growth that exceeded the average national economic growth from 2017 to 2019. These 6 provinces are located on Java Island, and the other 10 provinces are located outside Java Island. Thus, we also added the province location variable to our analysis. We employed panel data regression to estimate the data. This study finds that the region’s economic and population growth substantially impacts the region’s labor participation rate. While the manufacturing value-added, the labor productivity rate, and the location do not significantly affect the labor participation rate of the region. Since economic and population growth are significant factors influencing labor force participation, some government policies should prioritize promoting sustainable economic development and attracting people to the province. The result of the study on the effect of manufacturing value-added and labor productivity shows that it has no impact on labor participation rates. This suggests that policies aimed solely at boosting manufacturing output or labor productivity may not automatically translate into higher labor force participation. Policymakers should, therefore, diversify their focus to other sectors, such as services or technology, that might better encourage workforce engagement.